The anthelmintic praziquantel is a human serotoninergic G-protein-coupled receptor ligand. Issue 1 (December 2017) - Chan, John; Cupit, Pauline; Gunaratne, Gihan; McCorvy, John; Yang, Yang; Stoltz, Kristen; Webb, Thomas; Dosa, Peter; Roth, Bryan; Abagyan, Ruben; Cunningham, Charles; Marchant, Jonathan
Abstract Schistosomiasis is a debilitating tropical disease caused by infection with parasitic blood flukes. Approximately 260 million people are infected worldwide, underscoring the clinical and socioeconomic impact of this chronic infection. Schistosomiasis is treated with the drug praziquantel (PZQ), which has proved the therapeutic mainstay for over three decades of clinical use. However, the molecular target(s) of PZQ remain undefined. Here we identify a molecular target for the antischistosomal eutomer — (R) -PZQ — which functions as a partial agonist of the human serotoninergic 5HT2B receptor.(R) -PZQ modulation of serotoninergic signaling occurs over a concentration range sufficient to regulate vascular tone of the mesenteric blood vessels where the adult parasites reside within their host. These data establish(R) -PZQ as a G-protein-coupled receptor ligand and suggest that the efficacy of this clinically important anthelmintic is supported by a broad, cross species polypharmacology with PZQ modulating signaling events in both host and parasite. Schistosomiasis is caused by infection with the flatwormSchistosoma, and praziquantel is the drug of choice for its treatment. Here, Chan and colleagues identify praziquantel as a ligand for the human serotoninergic 5-HT2B G-protein-coupled receptor, and reveal a function for praziquantel as a regulator of vascular tone in treated hosts.